DEFORMASI DAN KEKUATAN GESER PASIR PADA PERCOBAAN GESER LANGSUNG - Reffanda Kurniawan (Universitas PGRI Palembang, 2014)
ABSTRACT The river is one of the water transport infrastructure have a crucial role in the movement for national development. One of which is to establish a means of supporting the court around the musi River, then it can be utilized as a place of tourism for the people of the city of Palembang and for trade. The Court is required to build the first retaining the musi River in order to shore up the buildings on it. One of the retaining required is turap. Turap is a part of the structure of the building thatserves as a holding ground and resist water ingress into the retting. Turap type, soil type and soil structure became a benchmark for shear strength of the soil at the cliff of Musi river retaining. In this paper, the kind of turap that is used to support the ground that is cantilever turap because the soil is on the musi River is a sandy silt. In addition analysis of depth turap also performed on development cliff of Musi river retaining 11-14 Ulu Palembang of South Sumatra.Keywords : Turap, River, Cantilever